2021
DOI: 10.7759/cureus.17645
|View full text |Cite
|
Sign up to set email alerts
|

Constraint-Induced Movement Therapy Combined With Botulinum Toxin for Post-stroke Spasticity: A Systematic Review and Meta-Analysis

Abstract: Stroke is considered one of the main causes of adult disability and the second most serious cause of death worldwide. The combination of botulinum toxin type A (BTX) with rehabilitation techniques such as modified constraint-induced movement therapy (mCIMT) has emerged as a highly efficient intervention for stroke patients to start synchronized motor function along with spasticity reduction. The current systematic review and meta-analysis were conducted in order to evaluate the available literature about the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
0
9
0
2
Order By: Relevance
“…There are currently no published papers on such treatments in patients with shoulder muscle spasticity, and some treatments, such as taping and casting, are not feasible in this anatomical region. The only treatments that have been described (in publications) after BoNT-A injection in shoulder muscles are transcutaneous electrical nerve stimulation ( 41 ) and constraint-induced movement therapy ( 42 ). However, the addition of passive mobilization, shoulder posturing, and, when possible, task-oriented active physiotherapy and occupational therapy were recommended by the expert team.…”
Section: Resultsmentioning
confidence: 99%
“…There are currently no published papers on such treatments in patients with shoulder muscle spasticity, and some treatments, such as taping and casting, are not feasible in this anatomical region. The only treatments that have been described (in publications) after BoNT-A injection in shoulder muscles are transcutaneous electrical nerve stimulation ( 41 ) and constraint-induced movement therapy ( 42 ). However, the addition of passive mobilization, shoulder posturing, and, when possible, task-oriented active physiotherapy and occupational therapy were recommended by the expert team.…”
Section: Resultsmentioning
confidence: 99%
“…Of the six RCTs that evaluated motor function, 23,[25][26][27][28][29] one found a significant improvement in motor function in the BoNT group before and after injection, 26 and two found between-group differences favoring BoNT groups. 25,27 Similarly, most reviews concluded that the effect of BoNT on motor function is unclear, 16,18 with one review reporting significant improvement 30 and another finding no significant difference between BoNT and controls. 20 The mixed results indicate that more research is necessary to draw conclusions on the effectiveness of BoNT on motor function.…”
Section: Effect Of Botulinum Toxin By Constructmentioning
confidence: 99%
“…Однако до настоящего времени продолжают обсуждаться оптимальные реабилитационные стратегии, и ряд исследований показывают эффективность и безопасность применения БТ комбинированной с роботизированными технологиями [42], двигательной терапией, вызванной ограничением движения (CIMT) [43], позиционированием, пассивным и активным растяжением спастических мышц [2], функциональной электростимуляцией [44][45][46], ортезированием [47]. Но, по данным шотландских исследователей, использование ортезов для запястья и паль-цев кисти в течение 4 нед.…”
Section: цереброваскулярные заболеванияunclassified
“…MEDITSINSKIY SOVET 2022;16 (21): [36][37][38][39][40][41][42][43][44][45] Cerebrovascular diseases ВВЕДЕНИЕ Церебральный инсульт (ЦИ) является третьей по значимости причиной инвалидности во всем мире [1,2]. Среди факторов, ограничиваю щих повседневное функционирование людей после инсульта, ведущее место занимают двигательные нарушения (статолокомоторные, дисфункция верхней конечности), которые включают спастичность, слабость (спастический парез) и контрактуры, а также когнитивные и эмоциональные расстройства [3][4][5][6][7].…”
unclassified